Anti-Müllerian Hormone Accelerates Pathological Process of Insulin Resistance in Polycystic Ovary Syndrome Patients - Li, Xiang-Juan; Wang, Hui; Lu, Dan-Yang; Yu, Tian-Tian; Ullah, Kamran; Shi, Xin-Yan; Shen, Yong-Hai; Fei, Xiao-Yang; Lin, Zhen-Yun; Huang, He-Feng; Lin, Xian-Hua (Hormone and Metabolic Research, 2021)
Insulin resistance (IR) is one of the most common features of polycystic ovary syndrome (PCOS), which is related to obesity. Whether increased anti-Müllerian hormone (AMH) levels in PCOS are involved in the pathogenesis of insulin resistance remains unclear. We investigated serum levels of leptin and AMH along with basic clinical and metabolic parameters in 114 PCOS patients and 181 non-PCOS women. PCOS patients presented higher fasting blood glucose, insulin concentrations and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) in addition to body mass index (BMI), lipids profiles and hormone levels. HOMA-IR showed a positive correlation with BMI, AMH, leptin, and low-density lipoprotein-cholesterol (LDL-c) levels. Interestingly, AMH is strongly positively correlated with HOMA-IR and insulin concentrations for 1st and 2nd hours of glucose treatment after fasting. Among PCOS women with BMI≥25 kg/m2, high AMH level group showed an increased HOMA-IR when compared to normal AMH level. However, among PCOS women with normal BMI, women with high AMH presented an elevated fasting insulin levels but not HOMA-IR when compared to normal AMH group. In vitro treatment of isolated islet cells with high concentration of leptin (200 ng/ml) or high leptin plus high concentration of AMH (1 ng/ml) significantly enhanced insulin secretion. Importantly, co-treatment of AMH plus leptin upregulates the expression of pro-apoptotic proteins, such as Bax, caspase-3, and caspase-8 after incubating with a high level of glucose. These results suggest that AMH may involve in the pathological process of pancreatic β-cells in obese PCOS women.
Keywords: anti-Mullerian hormone; insulin resistance; apoptosis; pancreatic islet cells